2009
DOI: 10.1161/circresaha.109.196287
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Infiltrating Prominin-1 + /CD133 + Progenitor Cells Represent the Cellular Source of Transforming Growth Factor β–Mediated Cardiac Fibrosis in Experimental Autoimmune Myocarditis

Abstract: Rationale: Myocardial fibrosis is a hallmark of inflammation-triggered end-stage heart disease, a common cause of heart failure in young patients. Objective: We used CD4 ؉ T-cell-mediated experimental autoimmune myocarditis model to determine the parameters regulating cardiac fibrosis in inflammatory heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 35 publications
3
73
0
1
Order By: Relevance
“…Being a circulating cell population, these CD133+ cells present an interesting cell pool that could be targeted to home to the site of injury and contribute to muscle repair. The ability of these cells to home and respond to injury has been reported in a number of studies, particularly in ischemic injury of the heart (Kania et al 2009;Kubo et al 2008;Voo et al 2008;Navarro-Sobrino et al 2010). Torrente et al (2004) have shown that the direct injection of CD133+ cells into dystrophic muscle improves skeletal muscle structure and replenishes the satellite cell pool, leading to a successful phase I clinical trial of autologous CD133+ cell injection in eight individuals with Duchenne muscular dystrophy .…”
Section: Recruitment Of Myogenic Progenitor Cellsmentioning
confidence: 98%
“…Being a circulating cell population, these CD133+ cells present an interesting cell pool that could be targeted to home to the site of injury and contribute to muscle repair. The ability of these cells to home and respond to injury has been reported in a number of studies, particularly in ischemic injury of the heart (Kania et al 2009;Kubo et al 2008;Voo et al 2008;Navarro-Sobrino et al 2010). Torrente et al (2004) have shown that the direct injection of CD133+ cells into dystrophic muscle improves skeletal muscle structure and replenishes the satellite cell pool, leading to a successful phase I clinical trial of autologous CD133+ cell injection in eight individuals with Duchenne muscular dystrophy .…”
Section: Recruitment Of Myogenic Progenitor Cellsmentioning
confidence: 98%
“…23 We therefore created chimeric mice to address the specific role of BM-derived cells in heart failure progression and tissue fibrosis. All chimeric mice were immunized with bmDCs, and for fibrosis development, animals were challenged with MyHC-␣/CFA.…”
Section: Myd88/il-1 Signaling In the Bm-derived Cellular Compartmentmentioning
confidence: 99%
“…These results raise a possibility that there is an intrinsic relationship between the two morphologically different cell types in the PLs. Indeed, it has been reported that CD133 + progenitors can differentiate into both fibroblasts and monocytes/macrophages in inflamed tissue (Kania et al, 2009). Therefore, it is very likely that there is a process of EPC-to-macrophage transition during the maturing of PLs.…”
Section: Discussionmentioning
confidence: 99%